2020
DOI: 10.3390/jcm9010218
|View full text |Cite
|
Sign up to set email alerts
|

Presbycusis: An Update on Cochlear Mechanisms and Therapies

Abstract: Age-related hearing impairment (ARHI), also referred to as presbycusis, is the most common sensory impairment seen in the elderly. As our cochlea, the peripheral organ of hearing, ages, we tend to experience a decline in hearing and are at greater risk of cochlear sensory-neural cell degeneration and exacerbated age-related hearing impairments, e.g., gradual hearing loss, deterioration in speech comprehension (especially in noisy environments), difficulty in the localization sound sources, and ringing sensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
147
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 137 publications
5
147
0
12
Order By: Relevance
“…Hearing measurements can be obtained in an easier manner using the C57BL/6 mice model than the other models. A recent study showed that aging is caused by oxidative stress due to changes in lifestyle, and the same study also described strategies to prevent ARHL and develop regenerative therapeutic substances [ 38 ]. This study aimed to reveal the phenotypes associated with hearing loss in a mouse model without other diseases, such as diabetes or vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing measurements can be obtained in an easier manner using the C57BL/6 mice model than the other models. A recent study showed that aging is caused by oxidative stress due to changes in lifestyle, and the same study also described strategies to prevent ARHL and develop regenerative therapeutic substances [ 38 ]. This study aimed to reveal the phenotypes associated with hearing loss in a mouse model without other diseases, such as diabetes or vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to congenital hearing loss, acquired hearing loss results from a non-genetic, exogenous, or idiopathic etiology. The most common acquired cause of SNHL in adults is presbycusis, the loss of hearing that accompanies the aging process (Keithley, 2019;Fischer et al, 2020;Wang and Puel, 2020). Other acquired causes of hearing loss in adults include noise exposure, ototoxic medications, and vascular changes resulting from chronic conditions (Cunningham and Tucci, 2017;Liberman and Kujawa, 2017).…”
Section: And Acquired Hearing Lossmentioning
confidence: 99%
“…Age-related hearing loss (AHL) or presbycusis is a universal sensory disorder in modern society and affects about 25-40% of people over 65 years (Tavanai & Mohammadkhani, 2017;Wang & Puel, 2020;Yamasoba et al, 2013). Hearing loss significantly affects the daily communication and contributes to social isolation, depression and possibly dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss significantly affects the daily communication and contributes to social isolation, depression and possibly dementia. Multiple factors such as genetic predisposition, epigenetic factors, aging and noise or ototoxic drug exposure are the causes of AHL (Tavanai & Mohammadkhani, 2017;Wang & Puel, 2020;Yamasoba et al, 2013). The underlying mechanisms of AHL include oxidative stress, mitochondrial DNA mutations, autophagy impairment and non-coding RNA disorders (Tavanai & Mohammadkhani, 2017;Wang & Puel, 2020;Yamasoba et al, 2013;Su et al, 2019).…”
Section: Introductionmentioning
confidence: 99%